European Roma Lives beyond Stereotypes - Rosenhaft, Eve; Sierra, María (Liverpool University Press, 2022)
This book, designed as a resource for scholars, educators, activists and non-specialist readers, presents the results of new research on the role of Romani groups in European culture and society since the nineteenth century. Its specific focus is on the ways in which Romani actors, in their interactions with non-Romanies, have contributed to shaping Europe's public spaces. Twelve chapters recount the experiences and accomplishments of individuals and families, from across Europe (England, France, Spain, Germany, Poland, Hungary, Romania and Finland) and Canada. All based on new research, and maintaining a focus on the real lives and activities of Romani people rather than on the perspective of the majority societies, these studies exemplify the creative presence of Romani people in the fields of politics, economics and culture. We see them as writers, artists and performers, political activists and resistance fighters, traders and entrepreneurs, circus and cinema managers and purveyors of popular science. Sensitive to the ambivalent position from which Roma act, the cases are linked and contextualized by a general introduction and by section introductions written by leading scholars of Romani studies with expertise in history, ethnography, musicology, literary and discourse studies and visual culture. The volume is richly illustrated, including many images that have never been published before, and includes an extensive bibliography / guide to further reading. Contributors to the volume: Begoña Barrera, Beatriz Carrillo de los Reyes, Malte Gasche, Paweł Lechowski, Anna G. Piotrowska, Laurence Prempain, Juan Pro, Eve Rosenhaft, Carolina García Sanz, María Sierra, and Tamara West.